Prevalence and Predisposing Factors of Non-infectious Cardiac Implantable Electronic Device Lead Masses as Incidental Finding During Transoesophageal Echocardiography: A Retrospective Cohort Study - Kuecken, Tanja; Jasaityte, Ruta; Bülow, Cara; Gross, Jessica; Haase-Fielitz, Anja; Neuss, Michael; Butter, Christian (Frontiers in Cardiovascular Medicine, 2022)
Objectives: In this study, we assessed the prevalence and predisposing factors of non-infectious CIED lead masses as incidental finding during transoesophageal echocardiography (TOE). Methods: In a retrospective single centre study, we analysed TOE examinations performed for indications other than infectious endocarditis in 141 patients with CIED. Patients with nonsuspicious leads and the ones with incidental non-infectious lead masses were compared in respect to clinical characteristics, anticoagulation, indication for TOE and CIED lead characteristics. The Odds ratios for non-infectious CIED lead masses were calculated. Results: Non-infectious CIED lead masses were detected in 39/141 (27.6%) patients. They were more often identified on ICD and CRT-D leads compared to pacemaker and CRT-P leads (OR 2.77 [95% CI 1.29-5.95], p=0,008). Lifespan of the CIEDs from the first implantation to the index TOE did not differ between both groups. Incidental CIED lead masses were more prevalent in patients who received their device for primary prevention of sudden cardiac death (43.2%) and for resynchronisation (63.6%) and less prevalent in patients with oral anticoagulation (OR 0.33 [95% CI 0.003-1.003], p= 0,048). Conclusion: Incidental non-infectious CIED lead masses were frequently found in TOE, with a highest prevalence in ICD and CRT-D devices implanted for patients with dilated cardiomyopathy. Patients with therapeutic anticoagulation had significantly lower prevalence of CIED lead masses than the ones without.